2019
DOI: 10.1002/ange.201903808
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical Sources and Availability of Amidophosphates on the Early Earth

Abstract: Phosphorylation of (pre)biotically relevant molecules in aqueous medium has recently been demonstrated using water-soluble diamidophosphate (DAP). Questions arise relating to the prebiotic availability of DAPand other amidophosphosphorus species on the early earth. Herein, we demonstrate that DAPa nd other amino-derivatives of phosphates/phosphite are generated when Fe 3 P( proxy for mineral schreibersite), condensed phosphates,a nd reduced oxidation state phosphorus compounds,w hichc ould have been available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…However, a recent report has described the synthesis of DAP by reacting the schreibersite surrogate Fe 3 P with concentrated (> 1 M) ammonia solutions. 25 The same study also showed that UV irradiation of HPO 3 2- in ammonia solution provides access to amidophosphate (H 2 N)PO 3 2- ). 25 …”
Section: Experimental Oxidation Of Reduced Phosphorus Speciesmentioning
confidence: 86%
See 1 more Smart Citation
“…However, a recent report has described the synthesis of DAP by reacting the schreibersite surrogate Fe 3 P with concentrated (> 1 M) ammonia solutions. 25 The same study also showed that UV irradiation of HPO 3 2- in ammonia solution provides access to amidophosphate (H 2 N)PO 3 2- ). 25 …”
Section: Experimental Oxidation Of Reduced Phosphorus Speciesmentioning
confidence: 86%
“… 25 The same study also showed that UV irradiation of HPO 3 2- in ammonia solution provides access to amidophosphate (H 2 N)PO 3 2- ). 25 …”
Section: Experimental Oxidation Of Reduced Phosphorus Speciesmentioning
confidence: 86%
“…However, CTMP is also formed via the oxidation of phosphite by hydroxyl radicals liberated via geochemical redox processes (Herschy et al, 2018) or from a reducing iron-rich impactor itself. It may also have emerged from phosphonamides which are becoming increasingly attractive as prebiotic phosphorylation agents (Gibard et al, 2019).…”
Section: Fig 2 (Continued)mentioning
confidence: 99%
“…In vivo, phosphate groups are added by a free-energy-rich molecule, ATP [24]. Prebiotic robust phosphorylating analogues, that are rich in energy, include trimetaphosphate ions, coming from volcanoes [25] [26], or phosphoramidates [27]. Their ammonolysis products can be substituted to ATP, as ATP is a far too complex assembly to have existed on the primordial Earth.…”
Section: Introductionmentioning
confidence: 99%